Novel Insights of Effects of Pregabalin on Neural Mechanisms of Intracortical Disinhibition in Physiopathology of Fibromyalgia: An Explanatory, Randomized, Double-Blind Crossover Study - Deitos, Alícia; Soldatelli, Matheus Dorigatti; Dussán-Sarria, Jairo Alberto; Souza, Andressa; da Silva Torres, Iraci Lucena; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2018)
Background: The fibromyalgia (FM) physiopathology involves an intracortical excitability/inhibition imbalance as measured by transcranial magnetic stimulation measures (TMS). TMS measures provide an index that can help to understand how the basal neuronal plasticity state (i.e., levels of the serum neurotrophins brain-derived neurotrophic factor (BDNF) and S100-B protein) could predict the effect of therapeutic approaches on the cortical circuitries. We used an experimental paradigm to evaluate if pregabalin could be more effective than a placebo, to improve the disinhibition in the cortical circuitries in FM patients, than in healthy subjects (HS). We compared the acute intragroup effect of pregabalin with the placebo in FM patients and healthy subjects (HS) on the current silent period (CSP) and short intracortical inhibition (SICI), which were the primary outcomes. Pain scores and the pain pressure threshold (PPT) were secondary outcomes. Methods: This study included 27 women (17 FM and 10 HS), with ages ranging from 19 to 65 years. In a blinded, placebo-controlled clinical trial, participants were randomized to receive, in a cross-over manner, oral pregabalin of 150 mg or a placebo. The cortical excitability pain measures were assessed before and 90 min after receiving the medication. Results: A generalized estimating equation (GEE) model revealed that in FM, pregabalin increased the CSP by 14.34% [confidence interval (CI) 95%; 4.02 to 21.63] and the placebo reduced the CSP by 1.58% (CI 95%; −57 to 25.9) (P = 0.00). Pregabalin reduced the SICI by 8.82% (CI 95%, −26 to 46.00) and the placebo increased it by 19.56% (CI 95%; 8.10 to 59.45; P = 0.02). Pregabalin also improved the pain measures. In the treatment group, the BDNF-adjusted index was positively correlated and the serum S100-B negatively correlated with the CSP, respectively. However, in the HS, pregabalin and the placebo did not induce a statistically significant effect in either intracortical excitability or pain measures. Conclusion: These results suggest that pregabalin’s effect on cortical neural networks occurs, particularly under basal neuronal hyperexcitability, because its impact on the cortical excitability and the pain measures was observed only in the FM group. This indicates that pregabalin increased the CSP to induce inhibition in specific neural networks, while it increased the SICI to improve the excitability in other neurobiological systems. Trial registration in clinicaltrials.gov Identifier: NCT02639533.